Screening and referral programs for diabetes and cardiovascular disease: Can community pharmacists bridge the care gap? - Melanie Livet; Amber Watson; Shweta Pathak; Courtney Humphries; Jessica Roller; Jon Easter (Exploratory Research in Clinical and Social Pharmacy)
Background and Objectives: Heart disease and diabetes are leading causes of death in the U.S., with timely screening, referrals, and education being critical for effective treatment. The Community-based Valued-driven Care Initiative (CVCI) aimed to develop, implement, and evaluate the feasibility of delivering patient-centered care interventions for high priority disease states in community pharmacies. This article focuses specifically on two of the selected interventions, both of which were screening and referral (S&R) programs for the prevention and treatment of cardiovascular disease (CVD) and diabetes (DM) respectively. This exploratory evaluation was designed as an effectiveness-implementation hybrid Type II study. Its objectives were to assess both implementation and preliminary program effectiveness using mixed data. Methods: Fifteen community pharmacies opted to implement one of the two programs over a 12-month period. Implementation feasibility involved examining program adoption rates by sites and patients; acceptability, appropriateness, feasibility, and intent to sustain use survey scores; and pharmacists' interviews. Program effectiveness was based on patient referral rates, physician follow-up communication rates, and perceived outcomes, collected via patient logs, surveys, and interviews. Results: Two of the 15 sites discontinued participation, yielding an 87 % adoption rate. Patient adoption varied based on contact and screening rates, due to differences in patient recruitment, staffing, and workflow. Pharmacist acceptability, compatibility, and feasibility remained high throughout implementation; however, only three pharmacy sites planned on continuing offering the programs. All at-risk patients were appropriately referred based on screening results, with 65 % having their screening results communicated to their primary healthcare providers. The programs were perceived as beneficial, increasing pharmacists' knowledge and motivation, enhancing relationships with patients, and producing an impact on patients'' health. Discussion: Results highlight the implementation feasibility and preliminary outcomes of delivering DM and CVD S&R programs in community pharmacies. However, despite these positive results, most pharmacies did not intend to continue the programs, underscoring the continued need for sustainable clinical services models in non-traditional settings. Success with broader implementation will require a paradigm shift in support of community pharmacists as clinical care extenders.